Did the Coronavirus Disease 2019 Lockdown Phase Influence Coastal Water Quality Parameters off Major Indian Cities and River Basins? - Aneesh Anandrao Lotliker; Sanjiba Kumar Baliarsingh; R. Venkat Shesu; Alakes Samanta; R. Chandrasekhar Naik; T. M. Balakrishnan Nair (Frontiers in Marine Science, 2021)
The end of the current decade experienced an outbreak of a new strain of coronavirus classified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) [coronavirus disease 2019 (COVID-19)] that spread across the globe within a short span of time and was declared as a global pandemic by the World Health Organization. In order to contain the spread of COVID-19, the Indian Government imposed lockdown in various phases, namely, the strict lockdown period (SLP) and relaxed lockdown period (RLP). The present study addresses changes in the magnitude of satellite-derived water quality parameters in the coastal waters off major Indian cities (Mumbai and Chennai) and river basins (Narmada, Mandovi-Zuari, Netravathi, Periyar, Kaveri, Krishna-Godavari, Mahanadi, and Hooghly) along the eastern Arabian Sea (EAS) and western Bay of Bengal (WBoB) during SLP and RLP. The daily climatology (2003–2019) and anomaly (2020) of different water quality parameters, viz ., chlorophyll- a (chl- a ), downwelling diffused attenuation coefficient (k d 490), and particulate organic carbon (POC) were used in the present study to eliminate seasonal biases and to unravel the signature of lockdown-induced changes in the magnitude of the above water quality parameters. During the total lockdown period, the magnitude of the above parameters reduced significantly in the coastal waters of both the EAS and the WBoB. However, this reduction was more significant in the coastal waters of the WBoB, attributed to a reduction in the supply of anthropogenic nutrients. Among different studied locations, the magnitude of water quality parameters significantly decreased off Chennai and Hooghly, during SLP, which subsequently increased during RLP probably due to reduction in anthropogenic material influx during SLP and increase during RLP. During RLP, the coastal waters off Mahanadi showed a maximum decrease in the magnitude of water quality parameters followed by Mandovi-Zuari, irrespective of these regions’ quantum of anthropogenic material input, possibly due to the higher response time of the ecosystem to reflect the reduction in anthropogenic perturbations. The satellite-retrieved water quality parameters have provided valuable insight to efficiently describe the changes in the health of the Indian coastal environment in terms of phytoplankton biomass and water clarity.